AN ANALYSIS STUDENTS’ PERCEPTION ON THE USE OF PAPER AND ELECTRONIC DICTIONARY - Agustinus Marjun (Universitas Kapuas, 2021)
This research paper has been designed to analyze students’ perception on the use of paper and electronic dictionary to the EFL students who studied on English study program in University of Kapuas Sintang. This study used 20 items of Questionnaire as the instrument for data collecting. There are sixteen students invited in this study. The result of this analysis reveals that electronic dictionary is mostly trending-use by the students in enhancing students’ learning as illustrated in mean score 4.50. Electronic dictionary has become convenient tool toward for the portability in which easy to be carried and the mean score at the level 4.00. The paper dictionary gets the highest frequency of agree 73 % toward the use of paper dictionary can enhance students’ learning. As an inference, the use of electronic dictionary and paper dictionary plays a significant impact for language learning whether good or not it is depending on the user to be selective and use it effectively. Keywords: student’s Perceptions, Electronic Dictionary, Paper Dictionary, EFL Learners,